State And Non-State Cross-Border Cooperation Between North Karelia And Its (Un) Familiar Russian Neighbors - Henrik D. Nielsen (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2021)
Russia has often been seen in a negative light and as a difficult place for foreigners to operate, both currently and in the past. To a large extent, this is also true for Finland, which has fought several wars against its eastern neighbor and whose border with Russia has been closed for years. However, Finland, and in particular North Karelia, also has a long history of cross-border cooperation with Russian partners.This paper seeks to analyze why North Karelian governmental and NGO actors choose to engage in cross-border cooperation with Russian counterparts and explain why they have been so successful.The answers are sought via a historical review of the relationship between Finland and Russia, in particular the role and importance of Karelia as a source of both conflict and consolidation. Furthermore, semi-structured interviews with Finnish cross-border cooperation actors are utilized in the analysis. The theoretical approach is grounded in (un)familiarity, which is used to explain the pull-push effects of the border.In conclusion, it was found that the Finnish actors harbor a historical feeling of connectedness and nostalgia towards the Karelian area which pulls them across the border. Because of the proximity they see cross-border cooperation as a natural extension of their work. Finally, the success is connected to the increased familiarity and close personal relations that have been build up over the years.